Modified PVA Film from Methanol-Soluble Phenolic Extracts of Spatholobus littoralis Hask as Active Pharmaceutical Packaging - Kadriadi, Kadriadi; Abral, Hairul; Mahardika, Melbi; Ilhamdi, Ilhamdi; Akmal, Akmal; Handayani, Dian; Yulianis, Yulianis; Kassim, Mohamad Haafiz Mohamad; Ariksa, Jeri (Journal of Fibers and Polymer Composites, 2026)
The development of active pharmaceutical packaging based on biodegradable materials is an important strategy to reduce dependence on single-use plastics and their environmental impact. Polyvinyl alcohol (PVA) is a potential biodegradable polymer, but it has limitations in terms of exposure to ultraviolet (UV) radiation and microbial contamination. This study aims to develop a modified PVA film with methanol-soluble phenolic extract of Spatholobus littoralis Hask as active pharmaceutical packaging with UV protection, antioxidant, and antibacterial functions. The phenolic extract was obtained through a maceration method using methanol as a solvent, while the PVA film was fabricated using the solution casting technique. The PVA film was modified with varying concentrations of phenolic extract of 0, 1.25, 2.5, and 5wt% (PPE0, PPE1.25, PPE2.5, and PPE5), then evaluated for its UV protection properties, antioxidant activity, and antibacterial activity. The results showed that the addition of S. littoralis phenolic extract was able to increase the ability of PVA films to block UV radiation completely (100%) in the 200–400 nm wavelength range. Antioxidant activity testing using the DPPH method showed an increase in free radical scavenging ability as the concentration of phenolic extract increased. In addition, the modified PVA film showed significant antibacterial activity against Staphylococcus aureus and Escherichia coli. These findings indicate that S. littoralis Hask phenolic extract has potential as a natural bioactive agent in the development of environmentally friendly and multifunctional active pharmaceutical packaging, with dual protection capabilities against UV degradation and microbial contamination. This research makes an important contribution to the development of sustainable pharmaceutical packaging materials based on renewable natural resources.